On queue with two types of general heterogeneous service with Bernoulli feedback. Issue 1 (1st January 2018) - Mahanta, Snigdha; Choudhury, Gautam
Abstract: This paper deals with the steady-state behavior of an M / G /1 queue with two types of general heterogeneous service to the arriving customers and Bernoulli feedback. We first derive the steady-state probability generating functions for the queue size distributions at a random epoch as well as at a departure epoch. Next, we derive the mean queue size at random epoch and the mean waiting time. Also, we obtain the mean busy period of this model and discuss some important particular cases.